The Meaning of Recreational Sports for Modern Society as A Lifestyle to Stay Active and Fit - Cahyo Wibowo; Sanfia Tesabela Messakh; Rival Aruna Tarigan (Journal Of Sport Education (JOPE), 2023)
This research aims to explore the meaning of recreational sports for modern society as a lifestyle to stay active and fit. This research is qualitative research with a phenomenological approach carried out in Salatiga City in several open and closed sports venues as well as in open sports facilities provided by the city government. Participants are residents of Salatiga City who do recreational sports. The total number of participants taken in this research was 25 respondents from various sports community groups and individually. Data collection techniques used in-dept interviews. The data analysis technique uses the method from Milles and Huberman which is divided into 4 stages, namely data collection, data reduction, data presentation, and drawing conclusions. The results found are that modern society does not know the definition of recreational sports well, they do recreational sports in their free time to maintain fitness, recreational sports are used as a lifestyle with the family, the environment and mass media are supporting factors in understanding and accessibility in doing recreational sports. The conclusion of this research is that modern society does not have a good understanding of recreational sports, but they consciously do it with internal motivation and also support from the environment, including family and mass media.